A mixed‐layer model perspective on stratocumulus steady states in a perturbed climate. (12th February 2014) - Gesso, S. Dal; Siebesma, A. P.; de Roode, S. R.; van Wessem, J. M.
<x xml:space="preserve">Abstract</x> Equilibrium states of stratocumulus are evaluated for a range of free tropospheric conditions in a mixed‐layer model framework using a number of different entrainment formulations. The equilibrium states show that a reduced lower tropospheric stability (LTS) and a drier free troposphere support a thicker cloud layer. Furthermore, cooler and drier free‐tropospheric conditions promote decoupling which is the first stage of stratocumulus break‐up into cumulus. The qualitative results hold for all the considered entrainment formulations, although the precise quantitative details of the boundary‐layer state do vary with the choice of entrainment parametrization. Perturbations of the equilibrium states by increasing the sea‐surface temperature while keeping the LTS and the free‐tropospheric relative humidity constant leads to cloud thinning and an increased occurrence of decoupling regime. These results are in line with recent large‐eddy simulation studies and increase the confidence in them by showing their validity for a large range of free tropospheric conditions.